THE WAYS OF THREATENED FETAL STATUS DIAGNOSTICS AND TREATMENT OPTIMIZATION: MATHEMATICAL ASPECT OF THE PROBLEM - Lakhno, I.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The article presents a matrix model of internal links in the system of mother-placenta-fetus. The existing diagnostic and therapeutic approaches of the fetoplacental insufficiency treatment were analyzed on its basis.